Analisis Penerapan Budaya Literasi Dalam Menumbuhkan Karakter Nasionalisme Kebangsaan Pada Masa Covid-19 Di SD Negeri 064972 Medan Denai - Sakinah Minta Ito, Samsul Bahri (Pusdikra Publishing, 2022)
The application of literacy culture in growing the character of nationalism during the covid-19 period has not been maximized due to the lack of interest in reading students and books. inadequate, the role of teachers in implementing literacy culture is still not maximized and learning during the covid-19 pandemic. This type of research is descriptive qualitative which seeks to clearly describe all the activities carried out by teachers to students in the application of the School Literacy Movement (GLS) in fifth grade students at SD Negeri 064972 Medan Denai. The author uses research procedures, including: interviews, documentation, questionnaires and observation. Based on the research conducted, it can be seen that: through the application of the literacy culture applied by the teacher, the character of nationalism during the covid-19 period can be fostered at SD Negeri 064972 Medan Denai, as can be seen from the enthusiasm for learning that continues to follow lessons in a pandemic condition through learning during, practicing religious teachings and social interaction among friends, obedient to parents, honest and mutual respect.